Mosby's pharmacy technician : principles and practice - Neumiller, Joshua J.; Hopper, Teresa (Instructor of pharmacy technology).; Steelman, Bobbi; Davis, Karin; Beale, Elaine; Mizner, James J.; eccarelli (St. Louis, Missouri : Elsevier, 2016)
Overview: Completely revised and rebuilt to correspond to the latest Pharmacy Technician industry standards, Mosby's Pharmacy Technician: Principles and Practice, 4th Edition includes all the information on pharmacy practice, anatomy and physiology, math calculation, and pharmacology you need to prepare for a successful career as a Pharmacy Technician. This approachable text includes new chapters on Medication Safety and Error Prevention and Communication and Role of the Technician with the Customer/Patient, along with new information on the latest pharmacy laws, HIPAA, USP 797, and much more. With its clear writing, expert insight, and engaging study tools, you will be able to develop a better understanding of the complex pharmaceutical content you need to pass the PTCB examination and succeed on the job. Comprehensive coverage of the most important subject areas taught in pharmacy technician programs provides comprehensive coverage of pharmacy practice, A&P, and pharmacology to prepare you for the PTCE and your future jobs. Technician Scenarios and Technician Scenario Check-up boxes highlight real-world examples. Comprehensive drug tables with pill images and label photos make learning drug information easier. Tech Notes and Tech Alerts offer practical references related to the chapter subject matter. Mini drug monographs provide the drug information you need for the drugs covered in the text. A&P content is included in the Body Systems section to help you build a foundation for how drugs work in the human body. Technician's Corner boxes include critical thinking exercises applicable to the chapter content. Pharmacist's Perspective boxes provide insights from the eye of the pharmacist. NEW! Update of pharmacy laws offers the latest issues and information found on the PTCB examination, including: HIPAA, the Medicare Modernization Act -- Recent legal changes due to the selling of pseudoephedrine products -- Issuance of multiple Schedule II prescriptions -- Pending legislation requirements for Medicaid prescriptions -- NEW! Completely revised TOC includes chapters on community pharmacy practice, institutional pharmacy practice, additional pharmacy practice settings, and individual chapters on the body systems. UNIQUE! New chapter on Medication Safety and Error Prevention to address the growing reports of technician-related medication errors. NEW! Chapter on Communication and Role of the Technician with the Customer/Patient highlights the increased customer-facing role that pharmacy technicians are now expected to have. NEW! Revised chapter on Math Calculations provides simple rules and examples for practice. NEW! Discussion of USP 797 covers the latest guidelines on all prescription and OTC medicines, dietary supplements, and other healthcare products manufactured and sold in the U.S. set forth by the United States Pharmacopeia (USP). NEW! Full-color photographs of hospital, retail, and home healthcare offers a visual of key areas and automation in the practice of pharmacy.
Section 1: Pharmacy Practice: -- History Of Medicine And Pharmacy: -- History of medicine -- History of pharmacy -- Pharmacy Law, Ethics, And Regulatory Agencies: -- Introduction -- FDA history -- Description of laws -- Food and Drug Administration/Drug Enforcement Administration -- Controlled substances -- Drug monographs -- Prescription regulation -- Special prescribing programs -- Pharmacy sites -- Occupational Safety and Health Administration -- Joint Commission -- Legal standards -- Competencies, Associations, And Settings For Technicians: -- Introduction -- Historical data -- Competencies -- National Healthcareer Association (NHA) -- Professionalism in the workplace -- Future of pharmacy technicians is bright! -- Communication And Role Of The Technician With The Customer/Patient: -- Introduction -- Communication -- Conclusion -- Dosage Forms And Routes Of Administration: -- Introduction -- Where did pharmacy abbreviations originate? -- Do not use list -- Dosing instructions -- Classifications of medications -- Classifications of drug sales -- Dosage forms -- Routes of administration -- Other considerations: form and function -- Use of excipients -- Manufactured products -- Packaging and storage requirements -- Medical terminology -- Conversions And Calculations: -- Introduction -- History of pharmacy calculations -- Roman numerals -- International time (military time) -- Temperature conversion between Fahrenheit and Celsius -- Basic math skills -- Measurement systems -- Calculations with liquid medication -- Business calculations -- Drug Information References: -- Introduction -- Researching a drug -- References used in pharmacy -- Pocket-sized reference books -- Electronic referencing -- Internet -- Journals and newsmagazines -- Additional types of information -- Considerations when choosing a reference -- Community Pharmacy Practice: -- Introduction -- Role of the pharmacy technician -- Prescription -- Prescription processing -- Prescription preparation -- Other pharmacy technician duties -- Pharmacy layout -- Communication -- Elderly patients -- Other pharmacy services -- Institutional Pharmacy Practice: -- Introduction -- Types of hospitals -- Hospital pharmacy standards and procedures -- Pharmacy and nursing staff relationship -- Hospital orders -- Institutional pharmacy technicians -- Additional Pharmacy Practice Settings: -- Introduction -- Advanced-level pharmacy technician opportunities -- Pharmacy technician positions of the future -- Bulk Repackaging And Non-Sterile Compounding: -- Introduction -- Bulk repackaging --- Non-sterile compounding -- Packaging -- Stability -- Documentation -- Safety -- Compounding professionalism -- Regulatory and quality control -- Veterinary medications -- Personnel training -- Compounding calculations -- Aseptic Technique And Sterile Compounding: -- Introduction -- Terminology used in pharmacy -- Standard precautions for a health care worker -- Supplies -- Routes of administration -- Medication delivery systems -- United States Pharmacopeia USP <797> -- Aseptic technique -- Education and training -- Pharmacy Billing And Inventory Management: -- Introduction -- Formulary and drug utilization -- Generic versus trade name drugs -- Types of private and group medical insurance plans -- Government-managed insurance programs -- Third-party billing -- Other methods of payment -- Inventory management -- Medication Safety And Error Prevention: -- Introduction -- Overview -- Five rights of medication safety -- What constitutes an error? -- Types of medication errors -- Responsibility for errors -- Where errors are made -- Why errors occur -- Drug interactions as a source of error -- Errors in the pharmacy -- Errors related to patient care -- Age-related errors -- Necessity of reporting errors -- Common pharmacy technology -- Patient dose-specific orders -- United States Pharmacopeia (USP) <797> regulations -- Mediation reconciliation -- Other considerations -- Training and education -- Conclusion -- Section 2: Pharmacology And Medications: -- Therapeutic Agents For The Nervous System: -- Nervous system -- Central nervous system -- Peripheral nervous system -- Conditions of the nervous system and their treatments -- Therapeutic Agents For The Endocrine System: -- Anatomy of the endocrine system -- Description of hormones and glands -- Functions of the endocrine glands -- Conditions of the endocrine system and their treatments -- Therapeutic Agents For The Musculoskeletal System: -- Anatomy and physiology of the skeletal system -- Anatomy and physiology of skeletal muscle -- Common conditions affecting the musculoskeletal system -- Other select medication classes that affect the musculoskeletal system -- Therapeutic Agents For The Cardiovascular System: -- Anatomy of the heart and vasculature system -- Regulation of the heart and vasculature -- Common medication classes used to treat cardiac conditions -- Conditions affecting the cardiovascular system -- Therapeutic Agents For The Respiratory System:-- Structure and function of the respiratory system -- Disorders and conditions of the respiratory system -- Therapeutic Agents For The Gastrointestinal System: -- Form and function of the gastrointestinal system -- Anatomy and physiology of the gastrointestinal system -- Conditions affecting the gastrointestinal system -- Therapeutic Agents For The Renal System: -- Anatomy and physiology of the renal and urological systems -- Conditions affecting the renal and urological systems -- Therapeutic Agents For The Reproductive System: -- Female reproductive system -- Conditions affecting the female reproductive systems -- Male reproductive system -- Conditions affecting the male reproductive system -- Sexually transmitted diseases -- Therapeutic Agents For The Immune System: -- Anatomy and physiology of the immune system -- Autoimmune disorders -- Transplant rejection -- Immunizations -- Therapeutic Agents For The Eyes, Ears, Nose, And Throat: -- Eyes (ophthalmic system) -- Conditions that affect the eye -- Ears (auditory system) -- Nose and sinuses -- Throat -- Therapeutic Agents For The Dermatological System: -- Anatomy and physiology of the dermatological system -- Common conditions affecting the dermatological system -- Therapeutic Agents For The Hematological System: -- Anatomy and physiology of the hematological system -- Conditions affecting the hematological system -- Over-The-Counter (OTC) Medications: -- Food and Drug Administration Regulations -- How a prescription drug becomes an over-the-counter drug -- Common conditions treated with OTC drugs -- Considerations for special populations -- Restricted OTC products -- Complementary And Alternative Medicine (CAM): -- What is complementary and alternative medicine (CAM)? -- Types of CAM -- Appendices: -- Appendix A: Review for the Pharmacy Certification Board (PTCB) examination -- Appendix B: Top 200 prescription drugs -- Appendix C: Top 30 herbal remedies -- Glossary -- Index.
Preceded by Mosby's pharmacy technician / Teresa Hopper. 3rd ed. c2012.
Includes bibliographical references and index.
Keywords: Pharmaceutical Services; Pharmacy; Anatomy; Pharmaceutical preparations; Pharmacists' Aides